Applications of polyimide coatings: a review - Sezer Hicyilmaz, Ayse; Celik Bedeloglu, Ayse (SN applied sciences, 2021)
Polyimides, high-performance polymers with superior properties such as high temperature stability, resistance to solvents and high strength, can be used in high-tech applications of the aerospace and aviation, medical or electronics industry in different forms (film, fiber, nanofiber, membrane, foam, adhesive or coating). Among these applications, coating has a special place and is used to develop advanced structures having high temperature resistance, flame retardancy and etc. for high tech industries via an economical and feasible way. Therefore, in this review, we aimed to report the broad application status of polyimide coatings by reviewing publications, patents and commercial products. Thus, this study can assist in selecting suitable polyimide types and production methods for polyimide coating applications and in understanding their applicability for future products.